2015
DOI: 10.3233/jad-150371
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Memory Complaints are Involved in the Relationship between Mood and Mild Cognitive Impairment

Abstract: Objectives: Subjective memory complaints (SMC) are common in older people and previous research has shown an association with mood problems, such as depression and anxiety. SMC form part of the criteria for many definitions of mild cognitive impairment (MCI), but there is controversy over whether they should be included as they may be related more strongly to mood than to objective cognitive impairment. This study aims to clarify the relationship between mood and SMC in people with MCI. Method: This paper repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 52 publications
(53 reference statements)
2
28
0
Order By: Relevance
“…48 Particular attention should be paid to subjects with MCI, who may recognize their own cognitive decline and, consequently, develop mood disorders and other afflictions, as well as demonstrate reduced self-esteem and affliction due to fear of developing dementia. 49 Surely, in these subjects, cognitive training should be conducted with full attention to the mental state of the individual, because the risk exists of aggravating their awareness of memory decline, exacerbating the sense of self-efficacy with consequent worsening of quality of life. 48 …”
Section: Discussionmentioning
confidence: 99%
“…48 Particular attention should be paid to subjects with MCI, who may recognize their own cognitive decline and, consequently, develop mood disorders and other afflictions, as well as demonstrate reduced self-esteem and affliction due to fear of developing dementia. 49 Surely, in these subjects, cognitive training should be conducted with full attention to the mental state of the individual, because the risk exists of aggravating their awareness of memory decline, exacerbating the sense of self-efficacy with consequent worsening of quality of life. 48 …”
Section: Discussionmentioning
confidence: 99%
“…SMCs were shown to correlate with informants' memory rating in adults diagnosed with Mild Cognitive Impairment (MCI) or dementia (Abner, Kryscio, Caban-Holt, & Schmitt, 2015; Buckley et al, 2015; Salem, Vogel, Ebstrup, Linneberg, & Waldemar, 2015), and to correlate with subjective mood (Yates, Clare, Woods, & Matthews, 2015). SMCs have also been associated with poorer verbal episodic memory performance (Gifford et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the cognitive aging literature, subjective cognitive impairment, or the patient's own appraisal of how their memory is functioning, has shown some success in adults with age-related cognitive disorders, such as mild cognitive impairment (MCI) and early stages of Alzheimer's disease [99-101], though not as reliably in cognitively normal older adults. One study has shown that the Montreal Cognitive Assessment (MoCA) was able to detect cognitive impairments in aging HIV-positive veterans [102].…”
Section: Clinical Implications Comorbidities and Management Formentioning
confidence: 99%